Direkte Schwefelbestimmung in Kohle mittels elektrothermischer Verdampfung gekoppelt mit Atomemissionsspektrometrie. Issue 10 (30th July 2014) - Bauer, Daniela; Vogt, Thomas; Lehmann, Franz; Otto, Matthias; Gutte, Heiner
<x xml:space="preserve">Abstract</x> The direct solid sample multielemental analysis of coal and its conversion products by electrothermal vaporization inductively coupled plasma optical emission spectrometry (ETV–ICP OES) is presented for analyzing sulfur. In addition to the determination of the total content, it is possible to keep track of the release of sulfur, based on controlled thermal decomposition of the sample in argon atmosphere and under ambient pressure. This could be fundamental for a possible speciation of sulfur in coal.